Sorry it took me so long: Latin America and rapid governments’ response to COVID-19 - Ian Rebouças Batista; Amanda Domingos; Rodrigo Lins (Ciências Sociais Unisinos)
Wen facing the COVID-19 pandemic, what was key to governments’ response velocity throughout Latin America? The region had more information on what to do to prevent the disease from spreading itself and social isolation was the most recommended measure to avoid contamination. Still, Latin American countries varied greatly on how fast they adopted strict social isolation measures. We deploy an explanatory work on which institutional designs collaborates with higher delay in governments’ adoption of these measures. Among the institutional variables considered, we find that our variable of interest (delay) correlates strongly and positively with democracy, negatively with concentration of power, and positively with GDP per capita. These might suggest that autocrats faced less institutional and moral constraints to act, while democratic leaders dealing with pluralism and accountability faced higher costs to implement such measures. Due to the small sample, we next investigate some countries’ experience looking for examples for the found correlations.